Evaluation of Competency Development in a Preparatory Program for Entry into Higher Education - Gaete-Rengifo, Rina Margarita; Parra-Díaz, Joel Alfonso (Revista Electrónica Educare, 2025)
Introduction. This original article is derived from the research study “Evaluation of Competency Development in Students of a Preparatory Program for Higher Education.” The study was conducted in the Araucanía region of Chile. Objective. The study aims to analyze the evaluation strategies used by the Early Academic Preparation Program teachers of the Universidad Católica de Temuco to assess competency development. Methodology. The study employed a qualitative methodological approach, with a case study design. The participants included faculty members responsible for implementing competency development courses. Data collection involved a documentary review of academic programs and evaluation instruments used by faculty, followed by content analysis of both types of documents. Results. The findings identified and described four evaluation strategies used in the program, as well as the significant presence of specific competency evaluation indicators and reduced incorporation of generic competencies in the evaluation instruments. Conclusions. The study identifies strengths and opportunities for improvement in evaluation strategies, particularly in the integration of generic competencies. Its findings highlight the importance of promoting self-regulation and academic reflection, incorporating self-assessment, peer assessment, and more structured feedback. Additionally, its results may be valuable for other institutions seeking to optimize their evaluation practices and enhance students’ comprehensive development.